Preparation, standardization and in vitro safety testing of Mycobacterium nosodes (Emtact- polyvalent nosode). Issue 3 (August 2016) - Joshi, Suvarna; Mukerjee, Sandeepan; Vaidya, Shashikant; Talele, Gitanjali; Chowdhary, Abhay; Shah, Rajesh
Abstract : Background: Most of the nosodes in the homeopathic pharmacopeia have been sourced from obscure pathological material over a century ago; of which no scientific documentation is available. Method: A method for preparation and standardization of univalent and polyvalent Mycobacterium nosodes (labeled as Emtact), using different strains of Mycobacterium tuberculosis was developed. The committee comprising microbiologists, scientist, pharmacist, homeopaths and clinicians had reviewed and approved the method of preparation of nosode. Preparation of the nosode was based on the reference in the Homeopathy Pharmacopoeia of India (HPI), group N-IV. Strains of M. tuberculosis viz. Standard strain H37Rv, multi-drug resistant (MDR) M. tuberculosis, Mycobacterium bovis (BCG vaccine) and Mycobacterium avium were identified, procured and documented. Twenty billion viable cells for each strain were taken for Original Stock Nosode (OSN). The original stock was prepared by suspending the microbial cells into water for injection (WFI) (1 ml). As per the Indian Pharmacopoeia (IP) monograph, sterility testing was done for different potencies. Polymerase Chain Reaction (PCR) was performed for 30c potency for detection of any DNA material of the source organisms. Result: A polyvalent (multi-strain) and univalent M. tuberculosis nosodes were prepared for research and clinical use. No growth of Mycobacterium was observed in any of the samples above 5c potency. The in-vitro testing for nosode (30c) was found to be free from any organism and DNA material. Conclusion: Mycobacterium nosodes sourced from individual strain and polyvalent Emtact nosode in vitro testing results found to be satisfactory for its handling and utilization. The nosode seems to be safe and may be tested further in vivo to explore its therapeutic application. Highlights: New Mycobacterium tuberculosis polyvalent (4 strains) nosode was prepared and standardized. Potency 6 and 30c is sterile and devoid of any bacterial or fungal contamination. Safety; nosode is free from organism and DNA material ( in vitro -testing).